Renate Wagner-Rieger (1921 ‒ 1980) — University Professor, Historicism Researcher, and Advocate for the Preservation of Vienna’s Townscape - Ingeborg Schemper - Sparholz; Caroline Mang (Peristil)
On the occasion of the 100th birthday of the art and architecture historian Renate Wagner-Rieger, the University of Vienna in cooperation with the Austrian Academy of Sciences organized an international conference in November 2021.1 Wagner-Rieger, who died in 1980, was the first female full professor at the Viennese Institute of Art History. On one hand, the conference showed the impact of her scholarly work in her time, and on the other hand her legacy and reception in current research. A second conference in early July 2022 focused on the genre of 19th-century sculpture, which as an art form closely related to architecture and was also an essential research interest of Wagner-Rieger. The 2021 conference was a further contribution of the Institute of Art History to its past. The focus of the institute’s self-reflection so far had contained several main representatives of the Viennese School, such as Rudolf Eitelberger, Alois Riegl, Julius Schlosser and Josef Strzygowski.